Pictorial review of tips and tricks for ureteroscopy and stone treatment: an essential guide for urologists from PETRA research consortium - ŞENER, TARIK EMRE (AME PUBL CO, 2019)
With an increase in the number of ureteroscopy (URS) procedures, URS is now performed more widely and is becoming a standard procedure for all urologists. There is also a rise in the complexity of these procedures and URS is now offered for treatment of stones as well as for diagnosis and treatment of urothelial tumours. We wanted to provide a 'pictorial review' of the 'tips and tricks' of URS, as the finer and technical details are often easier to understand and remember with images rather than through textual explanations.
Keywords: Ureteroscopy (URS); RIRS; stones; urolithiasis; tips and tricks; CLINICAL-RESEARCH OFFICE; URETERAL ACCESS SHEATH; FLEXIBLE URETEROSCOPY; MANAGEMENT; OUTCOMES; UROLITHIASIS; CARCINOMA; DISEASE